1956
DOI: 10.2307/2422331
|View full text |Cite
|
Sign up to set email alerts
|

A New Species of Rhamnocercinae

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The University of Notre Dame is collaborating with JSTOR to digitize, preserve and extend access to American Midland Naturalist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1969
1969
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…In the present paper, Rhamnocercus stichospinus Seamster and Monaco, 1956 is redescribed and illustrated. This species is recorded for the first time from the coastal zone of the South America Atlantic Ocean.…”
mentioning
confidence: 99%
“…In the present paper, Rhamnocercus stichospinus Seamster and Monaco, 1956 is redescribed and illustrated. This species is recorded for the first time from the coastal zone of the South America Atlantic Ocean.…”
mentioning
confidence: 99%
“…Hargis (1955) and Seamster and Monaco (1956) discussed the validity of Rhamnocercinae based on the origin of the echinodiscs and squamodiscs (see comment above). Bychowsky (1957) suggested that Rhamnocercinae and species of Lepidotrema are closely related due to the presence of spines in the peduncle and haptor, and considered squamodiscs to be homologous with these spines.…”
Section: Taxonomic Revisionmentioning
confidence: 99%
“…The presence of a sclerotized vagina, reported by Luque and Iannacone (1991), could not be confirmed due to the poor condition of the available specimen. Monaco, 1956) comb. n.…”
Section: Rhamnocercoides Menticirrhimentioning
confidence: 99%
See 2 more Smart Citations